Manifestations of Gender Injustice in Divorced Marriages: The Kabalutan Tradition - Susi Susilawati; Baliana Amir; Muhammad Ikbal; Rafika Nur; Sitti Fatimah Maddusila (Jambura Law Review, 2023)
This research entitled "Manifestations of Gender Injustice in the Tradition of Divorced Marriage in Kabalutan" is motivated by mass media information which states that in that village, there are many widows of various ages. From young to old age. It was also stated that in this village, it was easy to marry and divorce. Therefore, it is crucial to analyze this tradition from a gender perspective. So that it can be known which parties are harmed by this tradition, to be given socialization of what laws are needed there. The method is an empirical research method with primary data sources from traditional leaders and community leaders in the village. The stages are from surveys, observations, and conducting interviews, as well as collecting data for analysis and giving conclusions. The results of his research are that the term "widows' village" is a term that appeared during the population census in the 90s. At that time, there were many widows in Kabalutan Village for various reasons. But now, not anymore. Thus, the conclusion is that the stereotype of "Kampung Widow" towards Kabalutan Village, Talatako District, Tojo Una Una Regency is a manifestation of gender injustice. The people in the village are not comfortable with this labelling. In addition, it is not proven by the many widows there; it is also not the name of their village. Therefore, they asked to give only Kabalutan Village.